PERLAKUAN AKUNTANSI KARBON PADA PERUSAHAAN SEKTOR CONSUMER NON CYCLICALS DI INDONESIA - Angi, Yohana Febiani (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2024)
Corporate sector consumer non-cyclicals most affected by the Covid pandemic which was marked by a decline in shares in this sector so that what must be maintained in the company is the company value. Company value can be obtained by paying attention to the production process consumer non-cyclicals which leads to a green economy so it is important for companies to implement environmental accounting in financial reporting. The research objective is to evaluate, record, present and report environmental accounting based on PSAK. Assessment of the impact of environmental accounting on the company's financial ratios by calculating the offset of carbon absorption capacity due to production activities. Therefore, this research is limited to calculating the loss of carbon absorption capacity, the potential carbon produced and the impact of other carbon emissions on the production process.